Análise não linear de uma coluna esbelta em concreto armado usando o Método de Elementos Finitos e P-∆ - Souza, Régis Marciano de (2018)
The second-order effect of structures may be significant for understanding the behavior of the system. This research deals with the development of structural models for the study of the physical and geometric nonlinear behavior of slender columns in reinforced concrete. The main The main aim of this work is the comparative study between the formulations of the Iterative Process P-D and Finite Element Method, considering the nonlinear static analysis. Non-linear analyzes by the Finite Element Method were performed with the iterative-incremental process in the Newton Raphson formulation in ABAQUSTM software. The physical non-linearity was considered in a simplified way, as prescribed by standard ABNT NBR-6118. The Iterative Process P-D was implemented in the MATLAB® software. The parameter α and the coefficient Yz were used in the evaluation of second order effects. A comparison between the first and second order effects of the numerical simulations by using the Finite Element Method was performed. The numerical results revealed that the Iterative Process P-D can present divergent results from the numerical simulations by the Finite Element Method and that the second order effects are significant in thin columns of reinforced concrete.